Manajemen Pemerintahan Desa Dalam Meningkatkan Produktivitas BUMDes (Studi Kasus Desa Purwamekar Kecamatan Rawamerta Kabupaten Karawang) - Evi Priyanti; Dimas Rangga Agustin; Widya Indah Pradani; Diana Noviyanti (Ekonomikawan: Jurnal Ilmu Ekonomi dan Studi Pembangunan, 2021)
Village administration and BUMDes are separate but interconnected organizations. Based on the results of the research, the BUMDes of Purwamekar Village has several types of businesses, namely convection, livestock and fisheries as well as timber businesses. The management of BUMDes in Purwamekar Village actually has quite good results, which is proven by the existence of its superior business, namely the bag convection business. This bag convection business has successfully marketed its products to penetrate stores in the market, but currently the bag convection business is experiencing a very drastic decline due to the Covid 19 pandemic, so it has been forced to temporarily halt its production. BUMDes funds are currently being transferred by the village government to handle the Covid-19 pandemic in Purwamekar Village. The research method used in this study is a qualitative method, with this method the researchers obtained the results that the management of BUMDes in Purwamekar Village is currently not running well and has stopped due to the Covid-19 pandemic, the Purwamekar Village Government is allocating temporary BUMDes funds for handling covid-19.